Analysis of Constraints in Adoption of Improved Production Technology of Mandarin Cultivation (Indian Journal of Extension Education, 2013)
The present investigation was conducted with a sample size of 100 randomly selected respondents (orange growers) from 10 villages of purposively selected two blocks of Nagpur District of Maharashtra. The data were collected with the help of pre-tested structured interview schedule by conducting personal interview. The study revealed that majority of the farmers had medium level of adoption of improved production technology of mandarin cultivation . The study indicated that farmers had high adoption level of practices viz, irrigation management, time and spacing for planting, and low adoption practices viz, different varieties of orange, and rejuvenation of old orchards. So there is a need to adopt full improved recommended package of practices for increasing the productivity with quality of mandarin orange. The orange growers perceived the constraints like irregular fruit bearing, non availability of disease free improved planting materials etc. The present study clearly indicated the need to derive suitable matrimonies to minimise the constraints perceived by orange growers to increase the production and quality of mandarin orange.